Dust Removal from Solar PV Modules by Automated Cleaning Systems - Abdulsalam S. Alghamdi (Energies, 2019)
Dust accumulation on solar photovoltaic (PV) modules reduces light transmission from the outer surfaces to the solar cells reducing photon absorption and thus contributing to performance reduction of PV systems. In regions such as the Middle East where dust is prevalent and rainfall is scarce, remedial measures are needed to reduce such impacts. Currently, various techniques are being employed to address such sand soiling ranging from mechanical (brushing) to active and passive electrical interventions. This research focuses on mechanical approaches encompassing module vibration, air and water jets, and combinations of these. A reconfigurable pilot-scale testbed of 8 kWp PV plant was installed on a carport shading system within the campus of King Abdulaziz University (KAU), Jeddah, Saudi Arabia. The functional PV carport was configured to allow water recovery and re-use within the testbed. Here, we discuss the overall cleaning design philosophy and approach, systems design, and how multiple cleaning configurations can be realised within the overall PV carport. Results indicate that in this location, sand soiling has a significant effect on performance of PV modules on a timescale of days. In addition, water jets optimised for high volume and low pressure were effective at reducing sand soiling with array power output increasing by over 27%, whilst air jets and module vibration were less effective in reducing soiling to an acceptable level. Overall, the testbed has provided a new approach to testing a combination of cleaning solutions in the field coupled with used water recovery. The proposed approach is important, as currently, there are a large number of solar PV projects being built in Saudi Arabia with more being planned for the future.